THE ROLE OF CRITICAL THINKING IN ENGLISH LANGUAGE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Critical thinking has become one of the most important skills in twenty-firstcentury education. In English language teaching (ELT), critical thinking enables learners to analyze information, evaluate arguments, solve problems, and express their ideas effectively. This article examines the role of critical thinking in English language learning and discusses practical ways teachers can foster critical thinking skills in the classroom.
Keywords: The modern world requires individuals not only to acquire knowledge but also to think critically about the information they encounter. As English continues to serve as an international language, learners are expected to communicate ideas, participate in discussions, and evaluate diverse perspectives. Therefore, English language classrooms should promote both language proficiency and critical thinking skills.